The significance of CYP11A1 expression in skin physiology and pathology. (15th June 2021) - Slominski, R.M.; Raman, C.; Elmets, C.; Jetten, A.M.; Slominski, A.T.; Tuckey, R.C.
Abstract: CYP11A1, a member of the cytochrome P450 family, plays several key roles in the human body. It catalyzes the first and rate-limiting step in steroidogenesis, converting cholesterol to pregnenolone. Aside from the classical steroidogenic tissues such as the adrenals, gonads and placenta, CYP11A1 has also been found in the brain, gastrointestinal tract, immune systems, and finally the skin. CYP11A1 activity in the skin is regulated predominately by StAR protein and hence cholesterol levels in the mitochondria. However, UVB, UVC, CRH, ACTH, cAMP, and cytokines IL-1, IL-6 and TNFα can also regulate its expression and activity. Indeed, CYP11A1 plays several critical roles in the skin through its initiation of local steroidogenesis and specific metabolism of vitamin D, lumisterol, and 7-dehydrocholesterol. Products of these pathways regulate the protective barrier and skin immune functions in a context-dependent fashion through interactions with a number of receptors. Disturbances in CYP11A1 activity can lead to skin pathology. Highlights: CYP11A1 is expressed and enzymatically active in the skin. CYP11A1 initiates local steroidogenesis, secosteroidogenesis and 5, 7-diene metabolism. Cutaneous CYP11A1 is regulated by UVB, UVC, CRH, ACTH, c-AMP and cytokines. CYP11A1 plays a key role in regulation of the protective barrier and immune functions. Disturbances to CYP11A1 catalytic activity can lead to skin pathology.